Progressivity of Dum-Dum Kupat Inheritance Distribution in Java Community Perspective of Progressive Legal Theory Satjipto Rahardjo (Study in Pehserut Village, Sukomoro District, Nganjuk Regency) - M. Faizurrizqi Al-Farisi AD; Ziada Hilmi Hanifah; Nurul Kasanah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Distribution of inheritance using the method dum-dum kupat or equally is the division of inheritance by establish equal rights and shares to all heirs regardless of gender (male/female), this type of distribution model is mostly practised by the Javanese-Islamic community in Pehserut Village, Sukomoro District, Nganjuk Regency. Of course this if observed would be contrary to the provisions of inheritance in Sunni fiqh which applies a 2:1 ratio between men and women, but that does not mean that this method of dividing inheritance is wrong and contrary to the objectives of Islamic law, therefore the author wants to examine the side of inheritance. the progressive use of the inheritance distribution method dum-dum kupat, as well as the reasons the Javanese-Islamic community in Pehserut Village use this method more than using the inheritance provisions in Sunni fiqh and the Compilation of Islamic Law (KHI). The type of this research is empirical research (field research), collecting data using the interview method by determining the informants who are considered capable and have a relationship with the distribution of inheritance with this method dum-dum kupat. The results of this study indicate that the reason the Islamic-Javanese community in Pehserut Village uses the dum-dum kupat method as a way of distributing inheritance, among others, is because of the harmony factor and so that it is farthest from divisions between families, and this step of inheritance distribution can be said to be a form of progressivism. Law because it has fulfilled the aspects of the indicators; 1) Law for Humans, 2) Reject the status quo in law.